Assessing morphological diversity in Ethiopian yams (Dioscorea spp.) and its correspondence with folk taxonomy. Issue 5 (26th February 2021) - Asfaw, Bizuayehu Tesfaye; Worojie, Tsegaye Babege; Mengesha, Wendawek Abebe
Abstract : This study was conducted with the objective to investigate the diversity of wild and cultivated yams based on morphological characters and to assess its correspondence with folk taxonomy. The local classification system in South-west Ethiopia was studied by recording attributes of each landrace used in the folk taxonomy. Farmers differentiate various named plants based on variations in morphological, physiological, plant cycle and tuber quality attributes. A total of 75 accessions representing 30 differently named landraces were assessed using 37 qualitative and 13 quantitative characters. Principal component analysis showed that all the traits used were useful for capturing the variability among accessions. Traits such as leaf position, twining direction, type of tuber, petiole colour on young leaves, the entire wing traits, flowering and size of leaves were useful for capturing the variability among species. All the other traits were useful for capturing the variability among accessions of the same and different species. The cluster study separated the 75 accessions into four and five major clusters based on qualitative and quantitative traits, respectively. The study indicates that the local classification corresponds well with the morphological variability, but farmers somewhat underestimate the diversity of yams at lower level taxa. Our study shows the existence of high phenotypic polymorphism among accessions, which could be exploited, if improvement need arises. Yet, regarding the validity of member species in the D. cayenensis complex, many questions remain confusing, and will need to be solved with DNA-based studies.